English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

math helpp!!!

2007-04-22 09:53:41 · 3 answers · asked by Jimmy D 1 in Science & Mathematics Mathematics

3 answers

2(t + 3) - (3t - 1) = 4(3 - 2t) - 6

2t + 6 - 3t + 1 = 12 - 8t - 6

- t +7 = 6 - 8t

- t + 7 + t = 6 - 8t + t

7 = 6 - 7t

7 - 6 = 6 - 7t - 6

1 = - 7t

1 / -7 =- 7t / - 7

- 1/7 = t

- - - - - - - - s-

2007-04-22 10:35:28 · answer #1 · answered by SAMUEL D 7 · 0 0

2(t+3)-(3t-1)=4(3-2t)-6
2t+6-3t+1 = 12-8t-6
7-t = 6-8t
7t = -1
t = -1/7

2007-04-22 10:06:14 · answer #2 · answered by a c 2 · 0 0

2t+6-3t+1=12-8t-6
-t+7=6-8t
8t-t=6-7
7t=-1
t=-1/7

2007-04-22 12:31:54 · answer #3 · answered by Julie 3 · 0 0

fedest.com, questions and answers